(untitled) (PRÁXIS EM SAÚDE, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by changes in communication, sociability, and repetitive and stereotyped behaviors. Its prevalence has increased in Brazil, affecting approximately one in every 38 children. In this context, early intervention (EI) stands out as an essential approach to minimize the impacts caused by the disorder. Thus, the objective was to analyze the effects of EI on the neuropsychomotor development of children with ASD. This was an integrative literature review, in which eight studies related to the theme were identified. The results highlight impacts on neuropsychomotor development in its various dimensions, demonstrating the feasibility of EIs. It is concluded that EIs are feasible and effective in neuropsychomotor development, especially in early childhood. Despite the promising results, further studies focused on the applicability of different approaches are still needed.